Suppressing Ku70/Ku80 expression elevates homology-directed repair efficiency in primary fibroblasts. (June 2018) - Li, Guoling; Liu, Dewu; Zhang, Xianwei; Quan, Rong; Zhong, Cuili; Mo, Jianxin; Huang, Yaoqiang; Wang, Haoqiang; Ruan, Xiaofang; Xu, Zheng; Zheng, Enqin; Gu, Ting; et al.
Abstract: The main DNA repair pathways, nonhomologous end joining (NHEJ) and homology-directed repair (HDR), are complementary to each other; hence, interruptions of the NHEJ pathway can favor HDR. Improving HDR efficiency in animal primary fibroblasts can facilitate the generation of gene knock-in animals with agricultural and biomedical values by somatic cell nuclear transfer. In this study, we used siRNA to suppress the expression of Ku70 and Ku80, which are the key factors in NHEJ pathway, to investigate the effect of Ku silencing on the HDR efficiency in pig fetal fibroblasts. Down-regulation of Ku70 and Ku80 resulted in the promotion of the frequencies of multiple HDR pathways, including homologous recombination, single strand annealing, and single-stranded oligonucleotide-mediated DNA repair. We further evaluated the effects of Ku70 and Ku80 silencing on promoting HR-mediated knock-in efficiency in two porcine endogenous genes and found a significant increase in the amount of knock-in cells in Ku-silenced fibroblasts compared with control. The RNA interference strategy will benefit the generation of cell lines and organisms with precise genetic modifications.